Opening a Mountain: Koans of the Zen Masters. Steven Heine. - Keyworth, George A. (Buddhist Studies Review, 2003)
Opening a Mountain: Koans of the Zen Masters. Steven Heine. Oxford University Press, New York and Oxford 2001. xiv, 200 pp. £18.99. ISBN 019 513 586 5.